Study on influence of Saccharina japonica fermentation on chemical composition of mixed fodder for sea cucumber juveniles - Alexander M. Rogov (Известия ТИНРО)
Enzymatic processing of laminaria Saccharina japonica by industrial enzymes of proteolytic, mixed and amylolytic (cellulosolytic) action (CelloLux-F, Viscoflu MG, Allzyme РТ, Allzyme Vegpro, and Allzyme BG) is investigated. Alginase activity of enzyme preparations was measured by spectrophotometry with an anthrone reagent. Chemical composition of algae and fodder was determined by standard research methods. Total content of nitrogenous substances in the raw materials was determined by Kjeldahl method on the Kjeltec auto 10 SO Analyzer (Tecator, Japan). Alginic acid content was determined by titration method. Total lipid content was determined by Blight-Dayer method. The content of easily hydrolysable polysaccharides was determined by titration according to Bertrand. In the experiment, CelloLux-F had the highest alginase activity and Allzyme РТ had the lowest activity. Activity of other enzymes lowered in the order: Viscoflu MG > Allzyme BG > Allzyme Vegpro. The alginase activity of enzyme preparations determines their concentrations necessary for hydrolysis. Following to recommendations of the enzyme preparations manufacturers and cited information on their usage, the raw alga materials was processed during 6 hours under pH 6, gm 1 : 10-1 : 12 and temperature 55оC and 60оC. Under the processing, the main changes occur in quantitative composition of carbohydrates, namely the alginic acid content is reduced in 17.2-25.3 %, the fiber content is reduced in 38.5-74.0 % and the amount of easily hydrolyzable carbohydrates is increased in 2.7-3.7 times. Degree of the polysaccharides hydrolysis after processing with different enzyme preparations has lowered in the order: Allzyme BG (36.9 %) > CelloLux-F (35.5 %) > Allzyme Vegpro (34.6 %) > Viscoflu MG. The fermented algae were introduced into the mixed fodder formula. Using the processed alga instead of natural one allows to increase the content of easily hydrolyzable polysaccharides and to decrease the content of high-molecular polysaccharides as alginic acid and cellulose. Food efficiency of the mixed fodder was examined by biological testing with using pigmented sea cucumber juveniles with weigh 40-90 mg as the test-objects; the testing was conducted on the basis of aquaculture research complex Zapovednoe in the Kievka Bay (northwestern Japan Sea). The mixed fodder with natural laminaria from the Kiyevka Bay was used as a control in examination. Value of the mixed fodder was estimated by gain in body weight of test-objects. The tests showed the 3-5 times higher gains of the sea cucumber juveniles fed by the mixed fodder with fermented laminaria in compare with the control mixed fodder based on unprocessed algae.